Identification and inventory of bagworms on oil palm (Elaeis guineensis) in Sungai Rengit Village, Banyuasin District, South Sumatra, Indonesia - ERISE ANGGRAINI; HAPOSAN PURBA; SITI HERLINDA; SUSILAWATI SUSILAWATI; WEI HONG LAU; ARINAFRIL ARINAFRIL (Asian Journal of Agriculture, 2026)
Abstract. Anggraini E, Purba H, Herlinda S, Susilawati, Lau WH, Arinafril A. 2026. Identification and inventory of bagworms on oil palm (Elaeis guineensis) in Sungai Rengit Village, Banyuasin District, South Sumatra, Indonesia. Asian J Agric 10 (1): g100128. https://doi.org/10.13057/asianjagric/g100128. Oil palm (Elaeis guineensis) is one of Indonesia’s most important plantation commodities and a major contributor to the national economy. However, productivity is often constrained by pest infestations, particularly bagworms (Lepidoptera: Psychidae), which damage palm fronds and reduce photosynthetic capacity. This study aimed to identify bagworm species and quantify their abundance and infestation intensity in oil palm plantations in Sungai Rengit Village, Banyuasin District, South Sumatra, to provide baseline information supporting the development of appropriate integrated pest management strategies. Field observations were conducted using a diagonal sampling method across five plots, with 20 trees observed per plot (100 trees in total). Bagworms were collected manually and identified based on morphological characteristics. Four species were recorded: Pteroma sp., Metisa plana, Pteroma pendula, and Mahasena corbetti. Pteroma sp. was the dominant species (912 individuals), whereas M. corbetti had the lowest abundance (137 individuals). The overall mean infestation intensity across the five plots was 62%, calculated using the Townsend-Heuberger index, indicating severe foliar damage. Higher infestation levels were observed in edge plots and areas exposed to greater sunlight. These findings indicate a high level of bagworm infestation in the study area and variation in abundance across plots, possibly influenced by microenvironmental factors. This study provides baseline information on bagworm species composition, abundance, and infestation intensity, which is important to support the implementation of appropriate integrated pest management strategies in oil palm plantations.